Muslim family law in sub-Saharan Africa colonial legacies and post-colonial challenges - Jeppie, Shamil; Moosa, Ebrahim; Roberts, Richard L. 1949- (ISIM series on contemporary Muslim societies, 2010)
Muslim family law in Africa is as resilient today as it was during the first part of the twentieth century when millions of Africans were subject to French and British colonial administrations. And though these administrations have been gone for decades, their legacies continue to haunt Islamic legal schools, scholars, and practices in many African nations. In this fascinating volume, the editors bring together a number of essays that address key questions relating to Islamic law in Africa, documenting the struggles that Muslims have endured over the years and revealing Islamic law's place within the multicultural nation-states of contemporary Africa.